The Tuxá indigenous social network, interaction and exchange of information for the promotion of adaptive measures in the face of climate change - Dávalos, Nelson Eduardo Bernal; Rodrigues Filho, Saulo (Sustainability in Debate, 2022)
Studies show Social Network Analysis (SNA) as a successful methodology within the environmental sciences. In the present study, this methodology was implemented in the Tuxás indigenous community in Bahia-Brazil, to understand the configuration of interaction and information flow of the people and their multilevel relationship to face the environmental problem of drought. By creating networks by scale, we identify actors and their roles within the community, characterising the centrality of actors and their internal and external relationships to create adaptive strategic actions that strengthen the links between them and local and regional initiatives. For data collection, structured interviews were conducted with key informants using the snowball methodology. As a result, the SNA made it possible to identify links, bottlenecks and potential institutions to reduce the vulnerability of the traditional population and to identify adequate ways to promote adaptation and solve environmental problems.